PENGARUH SERVICE QUALITY DAN PERSEPSI HARGA TERHADAP LOYALITAS PENGGUNA JASA TRANSPORTASI MELALUI KEPUASAN PELANGGAN PADA GANESA TRANSPORT - I Gde Yudi Hendrawan3; Ni Luh Putu Juniantari; Ni Putu Nita Anggraini2 (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
Increasing competition demands business people to maximize the performance of a company. This research was conducted based on the phenomenon of customer fluctuations that make repeat orders, fluctuations in customer complaints on Ganesha Transport and the research gap. This study aims to reexamine the effect of service quality variables and price perceptions on the loyalty of users of transportation services through customer satisfaction This research was conducted at Ganesha Transport in Badung, Bali. This research is quantitative. The sampling technique in this study is non probability sampling with a purposive sampling method, with a total sample of 100 respondents. The data analysis technique in this research is PLS. The results showed that service quality has a positive and significant effect on customer satisfaction, price perception has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer loyalty, price perception has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer loyalty through customer satisfaction, and price perception has a positive and significant effect on customer loyalty through customer satisfaction.